TOKOH DAN CERITA SEBAGAI STRATEGI PRODUKSI PROGRAM NARASI PEOPLE - Tutupoho, Rizki Marwan; Yulistiani, Indriati (Synergy : Jurnal Ilmiah Multidisiplin, 2024)
This research aims to find out the production strategy for the Narasi People program. The method used in this research is a case study with a descriptive qualitative approach. This research explains several aspects related to the production strategy of the Narasi People program. Data collection was carried out through interviews with the Executive Producer of Narasi People as the main informant and two other informants. The results of the research showed that the Narasi People program had several strategic aspects in program packaging from pre-production to post-production. This strategy emphasizes the selection of sources and stories about the characters shown so that this show chooses a dominant form of format.